Evidence of organizational support in hospitals in the context of the COVID-19 pandemic: scoping review - Renata Santos Tito; Patricia Campos Pavan Baptista; Daniela Campos de Andrade Lourenção; Chennyfer Dobbins Abi Rached; Juliana Pereira Tavares de Melo; Edson José da Silva Junior; Cristiane Maria Talala Zogheib (Revista Gaúcha de Enfermagem)
ABSTRACT Objective: To map evidence of organizational support for healthcare professionals who worked in hospitals during the pandemic. Method: This is a scoping review, based on the framework established by Joanna Briggs Institute and the PRISMA-ScR protocol, registered in the Open Science Framework, under DOI: 10.17605/OSF.IO/2P7B4. Materials that presented evidence of organizational support measures offered to hospital healthcare professionals in the context of the pandemic were included. The databases CINAHL (Ebsco), EMBASE (Elsevier), LILACS (VHL), PubMed (NLM/NCBI), Science Direct (Elsevier), Academic Search Premier (Ebsco), PSYCiNFO (APA), SCOPUS (Elsevier), in addition to official websites of leading healthcare institutions with publications on the topic. Results: After pre-selection of 716 materials, 60 studies were included; whose results addressed the topics: financial support, in-service education, material resources and physical structure, psychological support, the role of leadership, and other institutional support measures. Conclusion: The pandemic scenario brought advances in relation to organizational support measures adopted in hospital institutions, highlighting the importance of investments in workplace support policies, not only during the pandemic period. Such actions can positively contribute to the provision of safe care for workers and patients.